Flavonoids from Pterogyne nitens as Zika virus NS2B-NS3 protease inhibitors - Lima, Caroline Sprengel [UNESP]; Mottin, Melina; de Assis, Leticia Ribeiro [UNESP]; Mesquita, Nathalya Cristina de Moraes Roso; Sousa, Bruna Katiele de Paula; Coimbra, Lais Durco; Santos, Karina Bispo-dos-; Zorn, Kimberley M.; Guido, Rafael V.C.; Ekins, Sean; Marques, Rafael Elias; Proença-Modena, José Luiz; et al. (Elsevier, 2021)
Although the widespread epidemic of Zika virus (ZIKV) and its neurological complications are well-known there are still no approved drugs available to treat this arboviral disease or vaccine to prevent the infection. Flavonoids from Pterogyne nitens have already demonstrated anti-flavivirus activity, although their target is unknown. In this study, we virtually screened an in-house database of 150 natural and semi-synthetic compounds against ZIKV NS2B-NS3 protease (NS2B-NS3p) using docking-based virtual screening, as part of the OpenZika project. As a result, we prioritized three flavonoids from P. nitens, quercetin, rutin and pedalitin, for experimental evaluation. We also used machine learning models, built with Assay Central® software, for predicting the activity and toxicity of these flavonoids. Biophysical and enzymatic assays generally agreed with the in silico predictions, confirming that the flavonoids inhibited ZIKV protease. The most promising hit, pedalitin, inhibited ZIKV NS2B-NS3p with an IC50 of 5 μM. In cell-based assays, pedalitin displayed significant activity at 250 and 500 µM, with slight toxicity in Vero cells. The results presented here demonstrate the potential of pedalitin as a candidate for hit-to-lead (H2L) optimization studies towards the discovery of antiviral drug candidates to treat ZIKV infections.
Keywords: Antiviral; Drug discovery; Emerging arboviruses; Enzyme inhibitors; Flavonoid; NS3 protein; Protease; Pterogyne nitens; Virtual screening; Zika virus